2014
DOI: 10.21608/jappmu.2014.70770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Different Levels of Fish Oil, Linseed Oil and Their Combination in Layer Diets on Egg Omega 3 Enrichment

Abstract: One hundred and five Mandara laying hens, 24 wks of age, were divided into seven experimental treatments to study the effect of dietary levels of fish oil (FO), linseed oil (LO) and their combination as a source of omega 3 on egg yolk omega three polyunsaturated fatty acids concentration on cholesterol and total lipids, and the productive performance and egg quality of laying hens. The experimental treatments were divided into seven treatments with three replicates each. The first treatment group was the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Linolenic acid was increased from 0.52% to 9.79%, and the n-6/n-3 PUFA ratio was decreased from 8.46 to 1.79. These results are in consent with those by Oliveira et al (2010) and Omar et al (2014). Brown et al (2018) found out that the laying hens' diet supplemented with the flaxseed oil did not affect either the external or the internal egg quality, except the yolk color.…”
Section: Table 4 the Influence Of The Linseed And Fish Oil On The Fasupporting
confidence: 85%
See 1 more Smart Citation
“…Linolenic acid was increased from 0.52% to 9.79%, and the n-6/n-3 PUFA ratio was decreased from 8.46 to 1.79. These results are in consent with those by Oliveira et al (2010) and Omar et al (2014). Brown et al (2018) found out that the laying hens' diet supplemented with the flaxseed oil did not affect either the external or the internal egg quality, except the yolk color.…”
Section: Table 4 the Influence Of The Linseed And Fish Oil On The Fasupporting
confidence: 85%
“…A consumer interest has increased not only due to a nutritional and dietary value but also due to a biofunctional value of eggs (Bubel et al, 2011). A composition modification of diets for the laying hens using the vegetable and animal oils can manipulate the lipid content in egg yolks (Kralik et al, 2005(Kralik et al, , 2008a(Kralik et al, , 2008b(Kralik et al, , 2018Yalçın et al, 2010;Petrović et al, 2012;Ehr et al, 2017). The n-3 polyunsaturated fatty acids (n-3 PUFAs), such as α-linolenic (ALA), eicosapentaenoic (EPA), and docosahexaenoic (DHA) acids, have a significant biologi-cal effect on health.…”
Section: Introductionmentioning
confidence: 99%